2021
DOI: 10.1182/blood.2020007876
|View full text |Cite
|
Sign up to set email alerts
|

Mouse multipotent progenitor 5 cells are located at the interphase between hematopoietic stem and progenitor cells

Abstract: Hematopoietic stem cells (HSCs) and distinct multipotent progenitor populations (MPP1-4) contained within the Lin- Sca-1+ c-Kit+ (LSK) compartment have previously been identified using diverse surface marker panels. Here, we phenotypically define and functionally characterize MPP5 (LSK CD34+ CD135- CD48- CD150-). Upon transplantation, MPP5 support initial emergency myelopoiesis followed by stable contribution to the lymphoid lineage. Since MPP5 are capable of generating MPP1-4, but not HSCs, they represent a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…While different multipotent precursors have been proposed, there is general consensus that only a small fraction of HSCs generates most of the hematopoietic progeny 39 , 40 . In line with this view, we showed that only a minor fraction of HSCs was cycling, and was therefore the likely source of most mature cells, potetially aligning with the recently described CD34 + CD135 − CD48 − CD150 − MPP5 41 .…”
Section: Discussionsupporting
confidence: 89%
“…While different multipotent precursors have been proposed, there is general consensus that only a small fraction of HSCs generates most of the hematopoietic progeny 39 , 40 . In line with this view, we showed that only a minor fraction of HSCs was cycling, and was therefore the likely source of most mature cells, potetially aligning with the recently described CD34 + CD135 − CD48 − CD150 − MPP5 41 .…”
Section: Discussionsupporting
confidence: 89%
“…[ 44 ] Sca‐1 is the other marker of mouse HSCs; Sca‐1‐positive cells can be found in the bone marrow, spleen, and peripheral blood, which also includes some progenitor cells in addition to HSCs. [ 45 ] Zhou et al. [ 46 ] reported that the transplant of Sca‐1‐positive hematopoietic stem/progenitor cells could reconstruct the hematopoietic function of mice suffering from lethal doses of radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The mutation frequencies were also determined in hematopoietic colonies derived from sorting single lineage − Sca-1 + c-Kit + CD34 − CD150 + CD48 − long-term hematopoietic stem cells (HSCs) and lineage − Sca-1 + c-Kit + CD34 + multipotent progenitors (MPPs) into 96-well plates (Supplementary Fig. S2 ) 19 , 20 . These cells were allowed to form colonies in MethoCult FG M3434 medium (STEMCELL Technologies, Vancouver, Canada) at 37 °C and 5% CO 2 for 14 days.…”
Section: Methodsmentioning
confidence: 99%